2011
DOI: 10.1021/jp1076356
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Products from the Pyrolysis of 2-Phenethyl Phenyl Ether

Abstract: This supplemental material contains Cartesian coordinates (Angstroms) for all structures at the CBS-QB3 level of theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 79 publications
(95 reference statements)
14
135
0
1
Order By: Relevance
“…A similar range of values have been reported by other researchers [73][74][75]. The Nimlos's research group [72] reported the formation of degradation products from the gas-phase pyrolysis of phenethyl phenyl ether and they concluded that the C−O homolysis occurred at high temperatures (>1000 °C), whereas the concerted retro-ene and Maccoll mechanisms were significant at lower temperatures (<600 °C).…”
Section: Ether Cleavage Mechanismssupporting
confidence: 82%
See 1 more Smart Citation
“…A similar range of values have been reported by other researchers [73][74][75]. The Nimlos's research group [72] reported the formation of degradation products from the gas-phase pyrolysis of phenethyl phenyl ether and they concluded that the C−O homolysis occurred at high temperatures (>1000 °C), whereas the concerted retro-ene and Maccoll mechanisms were significant at lower temperatures (<600 °C).…”
Section: Ether Cleavage Mechanismssupporting
confidence: 82%
“…Several concerted (heterolytic) mechanisms have been proposed for β-ether bond cleavage [42,[72][73][74][75][76]. Klein and Virk [42] proposed a six membered retro-ene mechanism based on an analysis of the kinetics for the formation of styrene and phenol from phenethyl phenyl ether.…”
Section: Ether Cleavage Mechanismsmentioning
confidence: 99%
“…Initial pyrolysis mechanism of the lignin model dimer According to previous studies, both homolytic cleavage and concerted decomposition may occur during the initial pyrolysis of lignin model compounds [39,40]. In order to elucidate the possible initial pyrolysis mechanism of this lignin model dimer, the BDEs for the C b -O and C a -C b homolysis and the activation energy for the C b -O concerted decomposition are calculated and illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[7,8] Computational studies have begun to provide insight into individual reaction steps, as well as substituent effects, that would be challenging experimentally. [11,15,[24][25][26][27][28][29][30][31][32] FVP deuterium isotope studies of PPE found products associated with carbon-oxygen homolysis and 1,2-elimination. [7,8] At higher temperatures (above 500 8C), the carbon-carbon bond was also cleaved, but at a lower rate.…”
Section: Introductionmentioning
confidence: 99%